Barter, exchange, and value an anthropological approach - Humphrey, Caroline; Hugh-Jones, Stephen 1945- (Cambridge University Press, 1992)
This book concerns barter, a transaction in which objects are exchanged directly for one another without the use of money. Economists treat barter as an inefficient alternative to market exchange, and assume that it is normal only in 'primitive' economies or marks the breakdown of more developed exchange mechanisms. For their part, anthropologists have been more interested in the social and moral complexities of the 'gift', and treat barter dismissively as mere haggling. The authors of this collection do not accept that barter occupies a residual space between monetary and gift economies. Using accounts from different parts of the world, they aim to demonstrate that it is more than a simple and self-evident economic institution. Barter may constitute a mode of exchange with its own social characteristics occupying a specific moral space. This novel treatment of barter represents an original and topical addition to the literature on economic anthropology